(3WHbGJ GdTGaYjIs - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eejJ GdCMjGA hoeMji GdehGJ hoeYjO GdNdGFb s
(3BNQgG (B:s
(3dg GdMeO XGgQkG hHGWfkG hgh MSHfG hfYe Gdhcjd bGd GdeDda hGab GdaQGZ ef JMQjQg aj Gdjhe GdMGOj hGdYTQjf ef ThGd SfI JSY hSJjf hSHYeGFI hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3fSNI SGOSIs
(3hHBNQgG oebGHdI Ydi fSNI oebGHdI HCUd GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B203s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B91 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B107 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B273 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs